2017
DOI: 10.1155/2017/8026297
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Breast Self-Examination and Associated Factors among Female Debre Berhan University Students

Abstract: Background Breast cancer is the most prevalent form of cancer in Ethiopia of all female cancers. It is considered to be a progressive disease with a poor prognosis if detected late. Breast self-examination is an important prevention method of breast cancer. This study was aimed at assessing practice and associated factors of breast self-examination (BSE) among female Debre Berhan University students in Ethiopia. Methods A cross-sectional study was conducted in 2015 among 420 using self-administrated questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
112
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 10 publications
23
112
6
6
Order By: Relevance
“…5 It is the leading cancer among females with a 24.4% prevalence rate and 26,200 women died of breast cancer in 2014. 6 Thus, morbidity and mortality associated with breast cancer can be reduced through early detection by means of screening programs, which not only increase the chances for successful treatment and cure of the disease, but also improve chances of survival and lessens the need forinvasive treatment. 7 Breast self-examination (BSE) is the most important and recommended screening method for early detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 It is the leading cancer among females with a 24.4% prevalence rate and 26,200 women died of breast cancer in 2014. 6 Thus, morbidity and mortality associated with breast cancer can be reduced through early detection by means of screening programs, which not only increase the chances for successful treatment and cure of the disease, but also improve chances of survival and lessens the need forinvasive treatment. 7 Breast self-examination (BSE) is the most important and recommended screening method for early detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8 BSE is the process whereby women examine their breasts regularly to detect any breast mass in order to seek early medical attention. 6 It is one of the screening methods used to detect breast-related problems such as possible lumps, distortions, or swelling 2,9 and it is recommended for every woman above the age of 20 years to be done for 20 min once monthly, 2 between the 7th and 10th days of the menstrual cycle (2-3 days after the menses has gone), and goes a long way in detecting breast cancer at early stages of growth when there is a low risk of spread, ensuring a better prognosis when treated. 6 However, in Ethiopia, breast cancer screening practice among women was only 6.9%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slightly less prevalence (17.33% and 11.4% respectively) were reported in other Pakistani studies, [20,22] on the other hand, When comparing our findings with other Islamic countries, different studies has reported varying percentages such as Akhtari-Zavare in Hamedan iran [13] found that 37.5% of their participants' family member have had breast cancer however, another study by Ghodsi in Hamedan Iran reported that only 13% have such family history [23]. More or less similar statistics were reported by studies conducted in Jorden [24] and UAE [25] (12.5% and 9.2% respectively) whereas in African countries like Ethiopia and Cameron very low prevalence were reported (3% -3.5 %) [26,27].…”
Section: Reasonsmentioning
confidence: 76%
“…Likewise a study in Iran on 119 health professional claimed that 87.4% of the participants perform BSE and 39.5% perform it on regular monthly basis [32]. Various other global researches also reported deficiency in BSE practice among females [12,24,26,27,29,33].…”
Section: Reasonsmentioning
confidence: 99%